Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/cod.13462
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to antibiotics in drug reaction with eosinophilia and systemic symptoms (DRESS) from other culprits

Abstract: Background: Antibiotics have been implicated in the reactivation of exanthema and systemic involvement in drug reaction with eosinophilia and systemic symptoms (DRESS); however, it is not clear whether these patients become sensitized to the antibiotic.Objective: To evaluate if, after DRESS, patients become sensitized to antibiotics. Methods:We retrospectively reviewed the patch test (PT) data and clinical files of DRESS patients who were administered antibiotics during DRESS from other culprits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…Clinical entity characterized by high levels of eotaxin and IL‐5 in skin lesions (responsible for the recruitment of eosinophils), and by skin infiltration of CD4 + and CD8 + T cells 90 . A recently published work showed that if there is an exposure to antibiotics during the active phase of DRESS, it can trigger a sensitization to the administered drug; which is explained by the massive activation of reactive immune cells 91 . A later manuscript has shown that other drugs such as radiocontrast media, proton pumps inhibitors or analgesics could be also involved in DRESS relapses 46 …”
Section: Immunological Mechanisms In Dhrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical entity characterized by high levels of eotaxin and IL‐5 in skin lesions (responsible for the recruitment of eosinophils), and by skin infiltration of CD4 + and CD8 + T cells 90 . A recently published work showed that if there is an exposure to antibiotics during the active phase of DRESS, it can trigger a sensitization to the administered drug; which is explained by the massive activation of reactive immune cells 91 . A later manuscript has shown that other drugs such as radiocontrast media, proton pumps inhibitors or analgesics could be also involved in DRESS relapses 46 …”
Section: Immunological Mechanisms In Dhrsmentioning
confidence: 99%
“…90 A recently published work showed that if there is an exposure to antibiotics during the active phase of DRESS, it can trigger a sensitization to the administered drug; which is explained by the massive activation of reactive immune cells. 91 A later manuscript has shown that other drugs such as radiocontrast media, proton pumps inhibitors or analgesics could be also involved in DRESS relapses. 46 These relapses may be associated with unknown mechanisms, and, in most cases, patients tolerate the drug after the complete recovery.…”
Section: Dressmentioning
confidence: 99%
“…When evaluating drug allergy, not only the initial DRESS trigger should be considered, but also drugs that were administered during the active phase of DRESS, if involved in relapses. Santiago et al have recently shown that a large proportion of DRESS patients develop a new sensitization to antibiotics administered during DRESS [ 17 ]. Our data suggest that also other non-antibiotic drugs may cause relapses with detectable sensitization such as radio contrast agents, proton pump inhibitors and NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some patients showed a new T cell sensitization to the causing drug, leading to a multiple drug hypersensitivity syndrome (MDH) [14–16 ]. These patients are at risk of developing a drug hypersensitivity on re‐exposure [17 ], therefore, they have to avoid multiple structurally different drugs. Thus, the distinction between drug‐related relapse without proven sensitization and MDH is pivotal for the subsequent therapeutic management.…”
Section: Introductionmentioning
confidence: 99%
“…For culprit drugs, the median time to onset was 22 days (IQR 17-28). Drugs involved are shown in Table S1 (Supporting Information), including allopurinol (25%, median time to onset 19 days, IQR 17-24), sulfasalazine (20%, median 24 days, IQR 19-24) and carbamazepine (20%, median 28 days, IQR [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Case Characteristics In Each Onset Modalitymentioning
confidence: 99%